Lithium Niobate-Based Integrated Photonics Utilizing Photorefractive Effect - Tarjanyi, Norbert; Kacik, Daniel (Communications - Scientific letters of the University of Zilina, 2017)
Lithium niobate (LiNbO3) is an ideal material with many interesting properties for integrated photonics. Despite the rich set of properties the technology of lithium niobate integrated optics has not evolved as much as integrated optics in III-V semiconductors and silicon photonics. Future applications of LiNbO3 as an integrated optical platform require a technology that can materialize ultracompact and efficient optical circuits on the material. To achieve the goal two possible approaches can be considered: developing of tightly-confined lithium niobate photonic devices and circuits on silicon substrates by hybrid technologies and, developing pure lithium niobate photonic devices employing strong photorefractive effect. The latter approach is in more details discussed in the contribution and concrete examples of practically realized photonic structures are presented.